PENGARUH KONDISI BUAH MENTAH DAN BUAH LUKA TERHADAP NILAI DOBI (DETERIORATION OF BLEACHIBILITY INDEX) DAN KANDUNGAN β-KAROTEN - M.Hendra ginting; Ika Ucha Pradifta; Dina Rusmawati (Institut Teknologi Sawit Indonesia, 2018)
DOBI (Deterioration Of Bleachibility Index) or purity power index is the ratio of carotene and secondary oxidation products to CPO (Crude Palm Oil). Caroten is one of the minor component that present in the oil. The main components of carotene are α- and β-carotene. The purpose of this study was to determine the eﬀect of unripe fruits conditions and wounds to DOBI value and β-carotene content. The research has done at Palm Oil Mill Bagerpang and the Laboratory of IOPRI Medan. The results showed the condition of unripe fruit has a value of DOBI 3.06 indicates good quality CPO and wound conditions have a value of DOBI 2.88 and the condition of unripe fruit has β-carotene content of 600 ppm is still above the average compared to the wound.